Reversible OH-bond activation and amphoterism by metal-ligand cooperativity of calix[4]pyrrolato aluminate - Sigmund, Lukas M.; Greb, Lutz (Chemical science, 2020)
Most p-block metal amides irreversibly react with metal alkoxides when subjected to alcohols, making reversible transformations with OH-substrates a challenging task. Herein, we describe how the combination of a Lewis acidic square-planar-coordinated aluminum(III) center with metal-ligand cooperativity leverages unconventional reactivity toward protic substrates. Calix[4]pyrrolato aluminate performs OH-bond activation of primary, secondary, and tertiary aliphatic and aromatic alcohols, which can be fully reversed under reduced pressure. The products exhibit a new form of metal-ligand cooperative amphoterism and undergo counterintuitive substitution reactions of a polar covalent Al-O bond by a dative Al-N bond. A comprehensive mechanistic picture of all processes is buttressed by isolation of intermediates, spectroscopy, and computation. This study delineates how structural constraints can invert thermodynamics for seemingly simple addition reactions and invert common trends in bond energies.
Gesehen am 28.10.2020